2010
DOI: 10.1007/s11205-010-9582-y
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Wellbeing: The Case of Indigenous Australians

Abstract: Indigenous, Culture, Wellbeing, Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
116
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(128 citation statements)
references
References 23 publications
11
116
0
1
Order By: Relevance
“…Pointing out that many immigrant and refugee communities are characterised by other social values, they claim that the profession now must 'question the primacy of Western (modernist) values and to rethink just what is universal' (Gray & Coates 2010, p. 21, emphasis in original). The risks inherent in a social work implementing western-based ideas about 'the best interest of the child' among culturally different groups are illustrated, for example, by the child protection interventions among Aboriginals in Australia during the first half of the twentieth century, where many children (now known as the Stolen Generation) were separated from their families and taken into custody (Dockery, 2010;Thorpe, 1994).…”
Section: Current Debate In Social Work: Culturally Appropriate Practimentioning
confidence: 99%
“…Pointing out that many immigrant and refugee communities are characterised by other social values, they claim that the profession now must 'question the primacy of Western (modernist) values and to rethink just what is universal' (Gray & Coates 2010, p. 21, emphasis in original). The risks inherent in a social work implementing western-based ideas about 'the best interest of the child' among culturally different groups are illustrated, for example, by the child protection interventions among Aboriginals in Australia during the first half of the twentieth century, where many children (now known as the Stolen Generation) were separated from their families and taken into custody (Dockery, 2010;Thorpe, 1994).…”
Section: Current Debate In Social Work: Culturally Appropriate Practimentioning
confidence: 99%
“…Community well-being Compound term encompassing mental, physical, social, and cultural health (Zubrick et al 2004, Carson et al 2007, Dockery 2010, Biddle and Swee 2012. 5 Effort Motivation, time, energy, and resources expended by the residential population to obtain food resources (McCarthy and McArthur 1960, Meehan 1982, Altman 1987, Walsh 2008, Codding et al 2011.…”
mentioning
confidence: 99%
“…traditional lifestyle has been associated with significant health benefits for Indigenous Australians (Burgess et al 2008;O'Dea 1984), and an association has been found between cultural attachment and positive outcomes in health, psychological wellbeing, substance abuse, and employment (Dockery 2009(Dockery , 2011. It is important to identify what works in recovery from substance abuse for Indigenous Australians, including identifying cultural drivers of resilience and health gains (National Health and Medical Research Council 2002).…”
mentioning
confidence: 99%